Laparoscopic Removal of a Copper Intrauterine Device from the Sigmoid Colon - Zeino, M.Y. (Society of Laparoendoscopic Surgeons, 2011)
IUD translocation to the sigmoid colon after uterine perforation is a rare but serious event. Removal of the IUD in such a situation has been recommended because of the risk of complication, such as fistula formation and colonic perforation. We present the case of a 43-year-old female with a copper T380A IUD embedded in the sigmoid colon, which was removed with minimally invasive techniques.